The Role of Millenial Liberica Coffee Farmers on Sustainability Community in West Tanjung Jabung - Banu Subagyo; Amirudin Amirudin; Lasno Lasno; Muhammad Yuda Ramdhani; Mohammad Iman Mahditama; Stefani Paskalian Widiyani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
This article is result of action research about the Millennial Farmer and Non-state Actor in the Development of Liberica Coffee in West Tanjung Jabung Regency in Jambi Province. The research is aimed at revealing the role of younger generation farmers and the support of non-state actors in developing a coffee industry amid the decreasing number of coffee farmers in the area, where only 8 percent of them are millennials. The data collection was conducted from May to July 2021. The research uses Bourdieu theory (1993,1998) about farmer’s practice based on certain motivations and the involvement of other actors. Based on the theory and direct observation, the study reveals that coffee has become a part of millennial’s lifestyle. The growing trend on coffee consumption provides a moment for coffee farmers to improve their products. Sungai Terap Village, Betara District, consists of peatland area and used to be main liberica coffee producer. However, liberica coffee has become less favorite commodities compared to palm oil, coconut and betel nut. As the coffee has been back on trend, millennial farmer Muhammad Firdaus is committed to develop the coffee business. Supported by PetroChina International Jabung Ltd., an upstream oil and gas company, Firdaus vows to increase the economic potential behind coffee business in his hometown.